A digital anatomical study of the corona mortis in females. Issue 2 (4th March 2017) - Han, Yan; Liu, Ping; Chen, Chunlin; Duan, Hui; Chen, Lan; Xu, Yikai; Chen, Ruiying; Pan, Hongxin; Zhao, Chunmei; Tang, Lei
Abstract: It was a different study from traditional anatomy to construct three-dimensional (3D) model of the corona mortis (CMOR) through contrasted enhanced computed tomography (CT) scanning. This will provide an aid for the understanding of the fine anatomy of CMOR, as well as surgical produces. A medical image processing system was used to process computed tomography scanning data collected from 330 cases of woman patients. Accurate digital 3D models of the CMOR were used to study the incidence, location, and the morphological patterns. These models have a rotation of 360° and allow displaying from different views. The incidence was 51.1% for the venous CMOR, 14.1% for the arterial CMOR in the 660 sides pelvic wall and vessel models. The mean distance from the symphysis pubis for the venous CMOR was 66.87 mm, and 59.60 mm for the arterial CMOR. The morphological patterns we identified were classified in three types (I-III). The model of CMOR serves as a useful tool for the learning and investigation of the CMOR. In the future, the digital anatomical data can be beneficial to illustrating the operation approach and decreasing the surgical complications.